2011
DOI: 10.1097/ta.0b013e31820d1c69
|View full text |Cite
|
Sign up to set email alerts
|

Observation for Nonoperative Management of Blunt Liver Injuries: How Long Is Long Enough?

Abstract: The length of observation should be based solely on clinical criteria. Patients with liver injuries may be safely discharged home in the presence of a normal abdominal examination and stable hemoglobin, regardless of the grade of injury. This guideline is safe and reduces LOS without increasing morbidity or mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 16 publications
3
39
0
2
Order By: Relevance
“…Liver-specific complication rate is 10%. In many studies, nonoperative management failure rate is under 10% (13). Similarly, in our series hemodynamically stable patients with grade 4 injuries were treated non-operatively with success (Figure 1, 2).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Liver-specific complication rate is 10%. In many studies, nonoperative management failure rate is under 10% (13). Similarly, in our series hemodynamically stable patients with grade 4 injuries were treated non-operatively with success (Figure 1, 2).…”
Section: Discussionmentioning
confidence: 64%
“…In a study where CT findings in blunt abdominal trauma were compared with surgery results (n=78) the sensitivity of CT in detecting hollow organ injuries was 55.3% and the specificity was 92% (14). That is why imaging should be used to support clinical findings, during follow up of hollow organ injuries in abdominal trauma and surgical decisionmaking (13).…”
Section: Discussionmentioning
confidence: 99%
“…1) [22][23][24]. The reported success rates for nonoperative management of liver injury are generally greater than 85 % [22,[25][26][27][28][29][30][31]. Approximately 70-80 % of liver injuries can be safely managed nonoperatively; even in most of the severe injuries, the nonoperative management rate approaches 50 % [32][33][34].…”
Section: Nonoperative Managementmentioning
confidence: 99%
“…NOM of haemodynamically stable patients with a CT proven liver injury has a success rate of approximately 90% [57][58][59] and has reduced mortality in recent years. 60 Predictors of NOM failure include high-grade liver injuries and pooling of contrast 43 although a study by Velmahos et al revealed that only 2% of NOM failures were related to liver injury, reflecting a multiply injured patient group.…”
Section: Hepatic Injuriesmentioning
confidence: 99%
“…58 Parks et al identified 1.9 days as the average stay for successful NOM across all injury grades. 59 They concluded that haemodynamic status, physical examination and serial haemoglobin measurements can determine discharge safely as failures for haemorrhage occurred early and other failures developed in multiply injured inpatients. NOM is, however, not risk free.…”
Section: Hepatic Injuriesmentioning
confidence: 99%